2012
DOI: 10.1111/j.1365-2893.2012.01642.x
|View full text |Cite
|
Sign up to set email alerts
|

In situ hybridization for the detection of hepatitis C virus RNA in human liver tissue

Abstract: In situ hybridization (ISH) enables visualization of specific nucleic acid in morphologically preserved cells and tissue sections. Detection of the HCV genomes in clinical specimens is useful for differential diagnosis, particularly between recurrent HCV infection and acute cellular rejection in transplant specimens. We optimized an ISH protocol that demonstrated sensitivity and specificity for detecting genomic and replicative form of HCV RNA in tissue biopsies. Digoxigenin (Dig)-labelled sense and anti-sense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Thus, manipulation of miR‐181a and/or DUSP6 expression may represent a key intervention to strengthen and broaden CD4 + T‐cell responses in HCV‐infected individuals. Based on this study, our previous reports, and other investigators' work, we propose a model, depicted in Fig. , to illustrate the role and pathways involved in the HCV‐induced, miR‐181a‐mediated DUSP6 overexpression in CD4 + T cells to control T‐cell responses in the setting of chronic viral infection.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Thus, manipulation of miR‐181a and/or DUSP6 expression may represent a key intervention to strengthen and broaden CD4 + T‐cell responses in HCV‐infected individuals. Based on this study, our previous reports, and other investigators' work, we propose a model, depicted in Fig. , to illustrate the role and pathways involved in the HCV‐induced, miR‐181a‐mediated DUSP6 overexpression in CD4 + T cells to control T‐cell responses in the setting of chronic viral infection.…”
Section: Discussionmentioning
confidence: 79%
“…After decades of studying this immunomodulatory virus, it has become evident that HCV‐mediated T‐cell dysfunction plays a major role in viral persistence as well as disease progression . We have previously reported that CD4 + T cells play a pivotal role in the host immune responses to pathogenic infection and vaccination . In this study, we further explored the mechanisms of CD4 + T‐cell dysfunction in chronic HCV infection.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The previously reported HCV genotypes of 7 through 9 have been re-classified as subtypes of genotype 6 (8). Sequence inconsistency ranges from 31% to 33% among genotypes and from 20% to 25% among subtypes (9). Genotypes 1 to 3 show a worldwide distribution, whereas genotypes 4 to 6 are more geographically restricted (10).…”
Section: Introductionmentioning
confidence: 99%
“…In nested RT-PCR negative cases, ISH was negative or partially positive, suggesting that the detection threshold may depend on the virus load. Diffuse HCV expression pattern in the hepatocytes was already reported by Nuriya et al [15], Liang et al [33], and Li et al [34]. …”
Section: Discussionmentioning
confidence: 55%